Entrepreneurial ecosystem in India: Taking stock and looking ahead - Srivardhini K. Jha (IIMB Management Review, 2018)
This round table article takes stock of the Indian startup ecosystem against the backdrop of its meteoric rise in recent years. The discussion identifies several positive aspects of the ecosystem—a plethora of opportunities to explore, availability of ample venture funding, and a young, educated workforce. However, in order to live up to its promise, the ecosystem needs to focus on value creation as opposed to valuation, educate its young entrepreneurs, and develop tolerance for well-intentioned failure. It also needs to solve the unique problems of India and ensure that the startup movement is inclusive. Keywords: Entrepreneurship, Entrepreneurial ecosystem, India, Innovation, Startup, Entrepreneurial education, Gender issues, Venture financing